Familial Translocation (2;18) Ascertained Through Recurrent Spontaneous Abortions - Bağcı, Gülseren; Tepeli, Emre; Düzcan, Füsun; Çetin, Ozan; Alataş, Erkan (Gynecology Obstetrics & Reproductive Medicine, 2010)
We report a young woman who presented with a reproductive history of two recurrent spontaneous abortions. Genetic etiology of recurrent fetal loss is determined by the demonstration of parents' chromosomal constitution. Analysis of the family members from 2 generations revealed 3 phenotypically normal individuals carying the same reciprocal translocation. The great majority of apparently balanced translocations are associated with multiple miscarriages and normal phenotype. The proband's karyotype was identified as 46, XX, t (2;18) (p15; p11.2) by giemsa banding techniques. The karyotypes of the proband's father and brother are 46, XY, t (2;18) (p15;p11.2). Her sister had two spontaneus abortions, her chromosomal analysis could not be determined because she was living in another city. Cytogenetic studies of unbalanced miscarriages are difficult due to the growth failure of early loss and usually macerated abortions. Reciprocal translocations are of great clinical importance. The carriers of balanced reciprocal translocations have increased risk of creating gametes with unbalanced chromosome translocations leading to miscarriages or children with abnormalities. Genetic counseling and genetic testing is often offered o families carrying a translacation.